Information and Communication Technology Usage by SMEs in a Developing Country: An Environmental Perspective - Azam, Shah; Quaddus, Mohammed (ANZAM, 2012)
The paper addresses organisational usage of Information and Communication Technology (ICT) from a developing country perspective. Applying three dimensions of environmental pressures—coercive pressures, normative pressures and mimetic pressures—with the two fundamental antecedents of Technology Acceptance Model (TAM)—perceived usefulness and ease of use—this study attempts to look at the effects of external forces on the adoption and use of ICT by SMEs in Bangladesh. PLS based path modelling with a cross-sectional dataset of 557 SMEs in Bangladesh reveals a significant association of normative pressures, coercive pressures, perceived usefulness and perceived ease of use with SMEs intention to use ICT. The path analysis further demonstrates a strong and significant effect of intention on actual ICT usage behaviour. The study concludes with implications of the results.